2022
DOI: 10.1128/spectrum.02102-22
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Characterization of bla NDM -Harboring Conjugative Plasmids in Acinetobacter Species

Abstract: Conjugative plasmids harboring the bla NDM gene play a vital role in disseminating carbapenem resistance. In this study, we first report a conjugative plasmid, pNDM-YR7, in Acinetobacter junii .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This plasmid also encodes proteins involved in maintenance and transfer and 19 proteins with unknown functions. Our bioinformatics analysis did not reveal any gene encoding a Rep protein for the initiation of plasmid replication on the pAhaeAN54e plasmid or the other members of the pNDM-YR7 clade [14]; in this work, we identified the minimal region of the pAhaeAN54e plasmid necessary for plasmid replication by an experimental approach. This 834 bp region has an unusual organization in that it encodes three small peptides that are required for plasmid replication and maintenance.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…This plasmid also encodes proteins involved in maintenance and transfer and 19 proteins with unknown functions. Our bioinformatics analysis did not reveal any gene encoding a Rep protein for the initiation of plasmid replication on the pAhaeAN54e plasmid or the other members of the pNDM-YR7 clade [14]; in this work, we identified the minimal region of the pAhaeAN54e plasmid necessary for plasmid replication by an experimental approach. This 834 bp region has an unusual organization in that it encodes three small peptides that are required for plasmid replication and maintenance.…”
Section: Introductionmentioning
confidence: 85%
“…The blaNDM genes are frequently present in plasmids. In a recent work, Tang and coworkers studied a set of 62 Acinetobacter plasmids containing blaNDM genes [14]. The phylogenetic analysis of these strains revealed that these plasmids belong to two different clades: the pNDM-JN01-like clade and the pNDM-YR7-like clade.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations